An Emerging Distributed Work Arrangement: An Investigation of Computer-Based Supplemental Work at Home - Venkatesh, Alladi; Vitalari, Nicholas P. (Management Science, 1992)
Recent advances in information technology and changes in social and economic relationships have led individual workers and organizations to explore various types of distributed work arrangements. This paper examines a specific type of distributed work arrangement, supplemental work at home. This arrangement refers to full-time employees doing job-related work at home in the evenings and on weekends. Based on a theoretical analysis of supplemental work, data gathered from a 346 computer-owners and 104 nonowners are empirically examined. The results suggest that the amount of time spent on supplemental work is positively related to work self-determination variables (flexibility and control), portability of work tasks, the availability of a telecommunications link between the firm and the home, and household income, and negatively related to commuting time and the presence of children at home. The paper discusses the implications of supplemental work for organizational design and the employer-employee relationship, It concludes that compared to other types of work at home, supplemental work is one remote work arrangement that is likely to persist, especially for professionals and managers.